2023
DOI: 10.1016/j.adro.2022.100916
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic Analysis to Predict Histopathologically Confirmed Pseudoprogression in Glioblastoma Patients

Abstract: analysis to predict histopathologically confirmed pseudoprogression in glioblastoma patients, Advances in Radiation Oncology (2022), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The model combining delta-radiomics and lactate dehydrogenase had the highest performance (AUC, 0.82). Similarly, McKenney et al 98 demonstrated an improvement in the AUC of a machine-learning classifier on combining O 6 -methylguanine-DNA methyltransferase (MGMT) with radiomics to predict PsP, thereby demonstrating the association of molecular drivers such as lactate dehydrogenase and MGMT. An AUC of 0.81 with radiomics alone jumped to 0.89 with the addition of MGMT values.…”
Section: Using Radiomics To Predict and Distinguish Typical And Atypi...mentioning
confidence: 96%
“…The model combining delta-radiomics and lactate dehydrogenase had the highest performance (AUC, 0.82). Similarly, McKenney et al 98 demonstrated an improvement in the AUC of a machine-learning classifier on combining O 6 -methylguanine-DNA methyltransferase (MGMT) with radiomics to predict PsP, thereby demonstrating the association of molecular drivers such as lactate dehydrogenase and MGMT. An AUC of 0.81 with radiomics alone jumped to 0.89 with the addition of MGMT values.…”
Section: Using Radiomics To Predict and Distinguish Typical And Atypi...mentioning
confidence: 96%
“…Moreover, concerning intratumoral heterogeneity, radiomics is often referred as a sort of «virtual biopsy», since it allows to enrich the traditional diagnostic radiologic workflow with more information not detectable by human eye and associated with processes not included in radiologic workflow ( 15 ). Current radiomics studies in the glioma field have shown promising results in demonstrating correlations between MRI features and GBM differential diagnosis ( 16 ), molecular characteristics ( 17 , 18 ), and prognoses ( 11 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%